TO COMPETITIONS OF YOUNG VOLLEYBALL PLAYERS THE IMPORTANCE OF PREPARATION - Madaminov Oribdjan Nishanbayevich (Proximus Journal Publishing, 2025)
This methodical guide summarizes the theoretical knowledge of the content of the general education school's "Volleyball" section of the physical education program, and is intended for use in the training of the volleyball groups of secondary schools. It can be used by students of physical culture, physical education teachers of masters and secondary schools, coaches of primary training groups of children and teenagers playing volleyball, organizers of physical education and all lovers of this sport
Keywords: Volleyball; Taem sports; Student cooperation